Food, energy and you - Yust, Larry (Los Angeles : Wexler Films [production company] ; Kuala Lumpur : Visual Resources [distributor])
This program demonstrates how our bodies use energy and where it comes from in the food we eat and also demonstrates the process by which food supplies energy
Writer and director, Larry Yust
Keywords: Food